2012
DOI: 10.1002/hed.23076
|View full text |Cite
|
Sign up to set email alerts
|

Orosphere assay: A method for propagation of head and neck cancer stem cells

Abstract: Background Recent evidence suggests that head and neck squamous cell carcinomas (HNSCC) harbor a small sub-population of highly tumorigenic cells, named cancer stem cells. A limiting factor in cancer stem cell research is the intrinsic difficulty of expanding cells in an undifferentiated state in vitro. Methods Here, we describe the development of the orosphere assay, a method for the study of putative head and neck cancer stem cells. An orosphere is defined as a non-adherent colony of cells sorted from prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 28 publications
1
58
0
1
Order By: Relevance
“…UM-SCC-1, UM-SCC-22A or UM-SCC-22B cells (1,000-3,000) were cultured in ultra-low attachment plates (Corning Inc., Corning, NY) with serum-free medium containing 0-50 ng/ml EGF, EC CM, or unconditioned medium for 7-15 days, as we showed (25). Orospheres, defined as non-adherent spheres of ≤25 cells, were photographed and counted under light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…UM-SCC-1, UM-SCC-22A or UM-SCC-22B cells (1,000-3,000) were cultured in ultra-low attachment plates (Corning Inc., Corning, NY) with serum-free medium containing 0-50 ng/ml EGF, EC CM, or unconditioned medium for 7-15 days, as we showed (25). Orospheres, defined as non-adherent spheres of ≤25 cells, were photographed and counted under light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…strategy is suitable for the propagation of head and neck cancer cells and can retain the stemness and self-renewal capacity of these cells [71].…”
Section: Suspension Culturementioning
confidence: 99%
“…Additional studies at the University of Michigan have identified various CSC markers in HNSCC (e.g. ALDH, CD44, Bmi-1; [9396]. Other markers also have been proposed (e.g.…”
Section: Clinical Relevance Of Cancer Stem Cells In Oral Tumorigenesismentioning
confidence: 99%